Exploiting the synergistic catalytic effects of CoPi nanostructures on Zr‐doped highly ordered TiO2 nanotubes for efficient solar water oxidation. (3rd May 2022) - Shaddad, Maged N.; Arunachalam, Prabhakarn; Amer, Mabrook S.; Al‐Mayouf, Abdullah M.; Hezam, Mahmoud; AlOraij, Haneen A.; Gimenez, Sixto
Summary: Photoelectrochemical (PEC) catalysis offers promising strategies for sustainable development. This study demonstrated the synergistic catalytic behavior of ZrO2 and a cobalt phosphate on anodized TiO2 nanotubes (TNTs), which significantly enhanced the PEC performance for visible‐light‐driven water splitting reactions. The sequential addition of ZrO2 /CoPi‐decorated TNTs was performed via electrodeposition and photoassisted electrodeposition. The substitution of Zr 4+ by Ti 4 can lead to the creation of oxygen vacancies, enabling electron trapping, reducing charge recombination, and thereby enhancing the charge transfer efficiency. Further, in the case of TNTs/ZrO2 /CoPi photoanode, the CoPi WOC functioned as a hole‐transfer relay to promote the water‐splitting reaction. Specifically, incorporating ZrO2 /CoPi rushes the surface reaction kinetics of TNTs and considerably improves charge transfer efficiency ( η CT   =  90%), photocurrent density (0.86 mA/cm 2 at 1.23 V RHE ) and durability were obtained. Further, the mechanistic examination by impedance measurements showed the enhanced charge transfer, and surface conductivity for prepared materials. The proposed method can be widely used to develop electrodes made of other materials to produce solar fuels. Abstract : The TNTs/ZrO2 /CoPi composite photoanode shows 4‐folds higher photoconversion efficiency than TNTs. The triple layer photoanodes provide well‐separated electron‐hole pairs, enhance the charge separation, and improve the hole transfer process for water oxidation.